2011
DOI: 10.1212/wnl.0b013e3182287aaf
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic dystonia and peripheral trauma

Abstract: Dystonia in association with peripheral trauma is a well-described clinical syndrome. The syndrome goes by many names--"traumatic" dystonia, "fixed" dystonia, peripherally induced dystonia, or complex region pain syndrome (CRPS) dystonia. We reviewed the role of peripheral trauma in the development of dystonia, focusing on 4 subtypes--cervical dystonia, focal limb dystonia, CRPS dystonia, and psychogenic dystonia. We show that peripheral trauma inducing, provoking, or precipitating structural changes within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 55 publications
0
39
1
Order By: Relevance
“…Because only a small group of patients develop dystonia in the setting of CRPS, some genetic predisposition might exist in patients who do develop this form of peripherally induced dystonia. 140 The presence of affective disorders and of psychogenic features in these patients has led some researchers to propose that dystonia in the setting of peripheral injury is largely of psychogenic origin 137,143 or a form of body integrity identity disorder. 144 More data are needed to better understand the CRPS dystonia syndrome.…”
Section: Peripherally Induced Dystonia and Complex Regional Painmentioning
confidence: 99%
“…Because only a small group of patients develop dystonia in the setting of CRPS, some genetic predisposition might exist in patients who do develop this form of peripherally induced dystonia. 140 The presence of affective disorders and of psychogenic features in these patients has led some researchers to propose that dystonia in the setting of peripheral injury is largely of psychogenic origin 137,143 or a form of body integrity identity disorder. 144 More data are needed to better understand the CRPS dystonia syndrome.…”
Section: Peripherally Induced Dystonia and Complex Regional Painmentioning
confidence: 99%
“…In a recent review of the literature on 713 patients with peripherally induced movement disorders [40], the authors find overlap with FMD in 15% of cases, but argue for presence of an organic movement disorder triggered by peripheral trauma in the majority of cases. An opposing view is taken by Hawley and Weiner [41], who make a case for a predominant psychogenic etiology in patients peripheral trauma associated dystonia. The use of electrophysiological methods such as measurements of cortical plasticity in this patient population [42] will hopefully provide a more definitive answer on the underlying pathophysiology in these cases.…”
Section: Updates On Post-traumatic Dystoniamentioning
confidence: 99%
“…Physiological mechanisms for traumatic dystonia have been suggested alongside psychogenic causes, but none has proven conclusive. 3,9 The vast majority of those subjected to local injury do not develop dystonia, so the trauma is not the sole cause, but it seems more probable that is the trigger to the appearance of dystonia in those predisposed to develop this illness. The hypothesis that peripheral injury might precipitate dystonia in those carrying the idiopathic torsion dystonia gene or genes is consistent with the findings of familial cases among patients with trauma induced dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, if as studies have shown there is a strong link between traumatic dystonia and psychogenic movement disorders, the psychological factors associated should be addressed as a matter of urgency. 3,10 Botulinum toxin A takes 2 days to commence working with its peak efficacy occurring in the second week. An instant effect following injection, as in this case, is therefore supportive of a functional component to the disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation